Internet of Things Based Cloud Smart Monitoring for Asthma Patient - Tabarek G. AL-Jaf; Emad H. Al-Hemiary (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The Internet of Things (IoT) is becoming the sinew of today and future technology. It can be exploited to make life much easier for human beings by taking the advantage that they have their own smart devices connected to the Internet. From this perspective, many society related issues like chronic diseases can be solved. In this paper, an IoT based remote monitoring for Asthma patients is designed and implemented. The work is initiated with a survey on Asthma chronic disease by asking specialists in this field then discussing how to monitor and control it using IoT technology. The prototype IoT Asthma monitoring system consists of a heart pulse sensor controlled by ESP8266. The data collected from the sensor is passed wirelessly to the ESP8266 in real time which in turn is send to the cloud using HTTP protocol. In the cloud, a MySQL database is used to store the received readings. The monitoring facility; hospital, doctor or person can browse the webpage written in PHP to monitor live update of patient condition. The work includes simulation of the network using packet tracer to verify its operation.